Protected Areas Isolation in the Chaco Region, Argentina - Matteucci, Silvia Diana (2012)
There is a general concern with regards to effectiveness of protected areas due to their progressive isolation caused by massive land use change in their surroundings. We examined the extent of natural vegetation fragmentation both within and around two protected areas over a period of 32 years, in the Argentine Chaco Region, in two contrasting ecoregions: Humid Chaco and Dry Chaco. We describe type and rate of change around each protected area, and discuss the potential implications for biodiversity conservation on the basis of a percolation/connectivity model for two endemic species. The results show that the rate and type of land use change is unique in each study area, and that the risk of isolation is imminent in both cases. This situation cancels the conservation objectives of protected areas, jeopardizing their effectiveness.